Effect of Board Accountability on Financial Performance of Selected SACCOs in Kiruhura District, Uganda. - Kyabarongo, Benon; Agaba, Moses; Byamukama, Eliab Mpora; Sunday, Arthur; Sekiwu, Denis (Kabale University, 2024)
Board accountability and Financial Performance are significant concepts among SACCOs in Uganda due to their involvement in the financial intermediation process. In spite of the several interventions by Bank Uganda, a number of banks and other financial institutions have failed to operate forcing the regulators to intervene to ensure sanity in the financial system. The purpose of this study was to investigate the effect of corporate governance on the financial performance of SACCOs in Kiruhura District, Uganda and the specific objective was; To examine the effect of board accountability on the financial performance of selected SACCOs in Kiruhura District, In this study, a cross-sectional survey research design was employed, adopting quantitative and qualitative approaches research approaches. A total population of 342 people was used at a confidence level of 95% or an error of 0.05 and the sample size was 184 respondents who involved the staff and members taken from the six SACCOs registered in Kiruhura district, Uganda as of January 2023. The obtained data for analysis was divided into two phases. First, descriptive statistics on the respondents and the preliminary data analysis were performed using SPSS version 20.0. These statistics included multicollinearity, mean and standard deviation, outliers and extreme values, and missing values in the second phase, the structural relationships between the variables in the suggested conceptual model were tested and examined using structural equation modeling (SEM). Jaffrey’s Amazing Statistical Program (JASP) version 0.17.2.0 was used to implement SEM. The findings of the study were: The effect of board accountability (BAC) on financial performance was found to have a negative effect ( = -0.908), implying that the data failed to support the direct relationship between BAC and FiP, thus not supporting H01, Therefore the study concludes that SACCOS will do less well financially the more its board assumes accountability for the company's decisions and communicates them openly to stakeholders. The study recommends that the board of directors should be more effective in ensuring that they communicate the decisions clearly and appropriately so that SACCO maximizes shareholders' wealth. SACCOs should seek the best strategies for communicating and sharing accountability feedback with SACCO members to generate maximum benefits for everyone